Democracy with Group Identity - Arye L. Hillman; Kfir Metsuyanim; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2015)
Group-based identity undermines democracy by impeding democratic change of government. A substantial literature has therefore studied how to make democracy consistent with group identity. We contribute to this literature by introducing the role of group decisiveness into voting incentives and mobilization of voters. In the elections that we study, for the same populations, accounting for income and other influences, group identity increased voter turnout on average by some 8 percentage points in local elections and decreased voter turnout by some 20 percentage points in national elections. We empirically investigate the effect of group identity on voter turnout and also evaluate whether group identity resulted in budgetary imbalance or replacement of local government because of disfunctionality. Our general contribution is to show how democracy can persist with group identity, although democracy in such instances differs from usual political competition.
Keywords: D03; D72; D74; H77; 330; voting turnout; voter decisiveness; expressive voting; instrumental voting; local government; Arab Spring